Accidental SO(10) axion from gauged flavour - Luca Di Luzio (Journal of High Energy Physics, 2020)
Abstract An accidental U(1) Peccei-Quinn (PQ) symmetry automatically arises in a class of SO(10) unified theories upon gauging the SU(3) f flavour group. The PQ symmetry is protected by the ℤ4 × ℤ3 center of SO(10) × SU(3) f up to effective operators of canonical dimension six. However, high-scale contributions to the axion potential posing a PQ quality problem arise only at d = 9. In the pre-inflationary PQ breaking scenario the axion mass window is predicted to be m a ∈ [7 × 10 −8 , 10 −3] eV, where the lower end is bounded by the seesaw scale and the upper end by iso-curvature fluctuations. A high-quality axion, that is immune to the PQ quality problem, is obtained for m a ≳ 2 0.02 eV. We finally offer a general perspective on the PQ quality problem in grand unified theories.